The Phenomenon of Bullying: Causes and Remedies - غالي شيماء شاكر (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
Bullying is one of the dangerous social phenomena that affect individuals and societies, as its negative effects are reflected on mental health, social behavior, and external behavior. Most often, it leaves long-term effects. My study of this phenomenon is divided into two axes. The first axis: the phenomenon of bullying in terms of its manifestations, causes, and its represented impacts on the individual’s personality, within the family, in school among students, between students and teachers, in society, and in the media. As for the second axis, it addresses the treatments of the phenomenon of bullying at different levels, in addition to mentioning the applications and methods that contribute to addressing this negative phenomenon. “Calling this phenomenon ‘bullying’ is, in my view, an exaggeration. Bullying is the behavior of tigers, that is, the behavior of my animal creatures — may God preserve you. This causes belittling and underestimating the human being, the student. Therefore, whenever we try to reconsider it, we can address the phenomenon of bullying.”.